The Synthesis of Superparamagnetic Cobalt Nanoparticles Encapsulated in Carbon Through High‐pressure CVD1. Issue 7 (27th March 2013) - Jaumann, Tony; Ibrahim, E. M. M.; Hampel, Silke; Maier, Diana; Leonhardt, Albrecht; Büchner, Bernd
Abstract : Superparamagnetic nanocomposites of carbon‐coated cobalt (Co@C) nanoparticles are synthesized through CVD by the use of cobaltocene and an additional hydrocarbon as the precursor. The nanocomposite is characterized by scanning electron microscopy (SEM), X‐ray diffraction (XRD), transmission electron microscopy (TEM), Raman spectroscopy (RS), and superconducting quantum interference device (SQUID) magnetometry. The cobalt nanoparticles exhibit face‐centered cubic (fcc) structure and an average size of about 4 nm within a narrow size distribution of 3–5 nm. They are tightly embedded in the carbon matrix in core/shell structures and well protected against oxidation. Magnetic results reveal superparamagnetic behavior with blocking temperature T B ∼ 140 K and a room temperature saturation magnetization of 79 emu g −1 . We evaluate synthesis parameters such as decomposition temperature, pressure, and ratio of cobalt to carbon in the gaseous precursor and show that they strongly affect the characteristics of the C matrix, the size of cobalt particles, and thus the magnetic properties of the nanocomposite. Abstract : The production of stable and super‐paramagnetic cobalt nanoparticles embedded in carbon through high‐pressure CVD is presented. A full characterization of morphology and magnetic properties is presented and the effect of synthesis parameters on the cobalt‐carbon nanocomposite is studied. The results can help to tailor the properties of stable magnetic nanostructures.